Neuro-fuzzy system for analysis the overall operations of companies in Thailand - Phichit Napook (2018)
© 2015 IEEE. This paper proposes the novel methodology using Neuro-fuzzy for analysis the overall operations of 982 companies in Thailand. The propose method consists of two parts. The first part is the clustering process to define classes of dataset using fuzzy system. The second part is the prediction process using the Neuro-fuzzy system to create the classification model for predict the turnover score of each class. The experimental results from the classification model show the high accuracy of the Neuro-fuzzy system. The merit of the proposed model can use as the tool for scoring the overall operations of companies.